Mental Health, Spirituality, and Religion in the Middle Ages and Early Modern Age - Classen, Albrecht 1956- (Berlin Boston, Mass De Gruyter, 2014)
Understanding mental health from a religious, literary, and philosophical point?of?view represents a critical component in current research on alternative approaches to well?being, spiritually and physically. This volume contains a selection of papers drawn from a conference at The University of Arizona in May 2013 addressing all these issues from a variety of perspectives, inviting us to consider them especially through a historical lens.
Understanding mental health from a religious, literary, and philosophical point?of?view represents a critical component in current research on alternative approaches to well?being, spiritually and physically. This volume contains a selection of papers drawn from a conference at The University of Arizona in May 2013 addressing all these issues from a variety of perspectives, inviting us to consider them especially through a historical lens. Albrecht Classen, The University of Arizona, Tucson, USA.
Literaturangaben
Archivierung/Langzeitarchivierung gewährleistet
Keywords: German Literature -- Middle High German, 1050-1500 -- History and criticism; German Literature -- Early modern, 1500-1700 -- History and criticism; Mental Illness -- History; Visions in literature; Visions -- History; Mental Illness -- History -- To 1500; Literature, Medieval -- History and criticism; Religion in literature; Mental illness in literature; Literature, Medieval; Mental Illness; German Literature; History of Medicine; Literatur, Rhetorik, Literaturwissenschaft; Medicine in Literature; Mental Disorders; Religion and Psychology; Religiosität; Visions; Konferenzschrift -- 2013 -- Tucson, Ariz; Konferenzschrift